2022
DOI: 10.1101/2022.06.26.497633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromosome level reference genome for European flat oyster (Ostrea edulis L.)

Abstract: The European flat oyster (Ostrea edulis L.) is a bivalve naturally distributed across Europe that was an integral part of human diets for centuries, until anthropogenic activities and disease outbreaks severely reduced wild populations. Despite a growing interest in genetic applications to support population management and aquaculture, a reference genome for this species is lacking to date. Here we report a chromosome-level assembly and annotation for the European Flat oyster genome, generated using Oxford Nan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 108 publications
3
6
0
Order By: Relevance
“…The down-regulation of those genes could indicate a lower capacity of immune response by the oyster. C1q domain containing proteins have been largely characterized in mollusk genomes, are characterized by a large diversity gene number across species (Mun et al, 2017; Gerdol et al, 2019, Peng et al, 2020; Farhat et al, 2022) and have been shown to be overrepresented in O. edulis genome (Gundappa et al, 2022the over-expression of genes involved in apoptosis is coherent with previous results obtained on O. edulis in response to B. ostreae (Gervais et al, 2019) or in C . virginica in response to Perkinsus marinus (Lau et al, 2018)…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The down-regulation of those genes could indicate a lower capacity of immune response by the oyster. C1q domain containing proteins have been largely characterized in mollusk genomes, are characterized by a large diversity gene number across species (Mun et al, 2017; Gerdol et al, 2019, Peng et al, 2020; Farhat et al, 2022) and have been shown to be overrepresented in O. edulis genome (Gundappa et al, 2022the over-expression of genes involved in apoptosis is coherent with previous results obtained on O. edulis in response to B. ostreae (Gervais et al, 2019) or in C . virginica in response to Perkinsus marinus (Lau et al, 2018)…”
Section: Discussionsupporting
confidence: 86%
“…A total of 35962 protein-coding genes were predicted from which 24302 genes were functionally annotated (e-value<0.001). The parameters of completeness and main genome features of the assembly are presented in Table 1 and are very close from those obtained in the OE_Roslin_V1 assembly (Gundappa et al, 2022). Phylogenetic tree confirms that Roscoff_O .…”
Section: Resultssupporting
confidence: 72%
“…The genotype concordance rate among replicates was 99.7%, demonstrating a high reproducibility of the genotyping assays. The flanking region of these markers were mapped to the O. edulis chromosome-level genome assembly ( Gundappa et al, 2022 ). Of the 11,808 SNPs, 10,025 had uniquely mapping probes and were retained for downstream analysis.…”
Section: Methodsmentioning
confidence: 99%
“…These resources have been applied to examine the genetic basis of growth ( Jones et al, 2014 ; Gutierrez et al, 2018 ; He et al, 2021 ), low salinity tolerance ( McCarty et al, 2022 ), disease resistance ( Gutierrez et al, 2020 ; Yang et al, 2022 ) and nutritional content ( Meng et al, 2019 ). For the European flat oyster, high-quality genomes have recently been released ( Boutet et al, 2022 ; Gundappa et al, 2022 ), which along with available high-throughput genotyping techniques (e.g., SNP arrays and genotype-by-sequencing approaches), provide the opportunity for gaining insight into the genomic architecture of relevant production traits. Most of the traits of economic importance in aquaculture species have a polygenic architecture ( Zenger et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…FUN_017843; Gundappa et al 2022). The predicted protein product of this gene contains an AAA domain, hence can bind and hydrolyse ATP (Lupas and Martin 2002).…”
Section: Genome-wide Association Analysis For Growth-related Traitsmentioning
confidence: 99%